The great divide: Transatlantic brothering and masonic internationalism, c. 1870–c. 1930. Issue 3 (3rd July 2019) - Berger, Joachim
ABSTRACT: This article demonstrates the interplay between national, international and transatlantic dimensions within fraternalism. From the late nineteenth century, masonic lodges took part in the broader push towards the formation of transnational organisations and institutions. They were mainly based in western and southwestern Europe. However, transatlantic channels were established that went beyond the individual and local level. The article analyses these waves of transatlantic brothering and relates them to the tides of confrontation and rapprochement between the United States and Europe. It argues that the First World War marked a moment of intensified interactions when English and French masonries rivalled over the Americans' favour, followed by a period in which transatlantic internationalist initiatives were shaped by masons based in New York. These inner-masonic alliances embraced the rationale of international relations in the realm of state policy and promised to overcome the divides between the various camps in European and World freemasonry.